Mitigation of Misstatement Risk on Stock Opname Findings - Sherly Lu' Lu' Ul Aini; Nayla Mir'atus Sa'adah; Alivia Zahra Aveninne; Muhammad Ghaza Alfarisi Bastaman; Ridwan Zulpi Agha (CV. ITTC INDONESIA, 2025)
This study examines the relationship between stock opname findings in inventory accounts and the risk of misstatement in financial statements, and designs effective mitigation strategies to reduce such risks. The objective is to develop a comprehensive understanding of the connection between stock opname findings and misstatement risk, while providing practical recommendations for mitigating these issues. The research employs a descriptive exploratory method through a literature review of related journals on stock opname audit and recent effective mitigation strategies. The findings reveal that discrepancies between inventory data within accounting systems and physical conditions are caused by factors including recording errors, weak internal controls, and human resource limitations. Proposed mitigation strategies involve implementing technologies such as RFID and barcode, strengthening internal controls and conducting intensive staff training, adopting integrated inventory management systems with real-time updates, and applying the Economic Order Quantity (EOQ) method integrated with forecasting. This research aims to serve as a practical reference for auditors and management to improve financial statement accuracy and contributes to academic development in inventory audit knowledge.